Peran Pengungkapan ESG dalam Meningkatkan Nilai Perusahaan dan Kinerja Keuangan di Sektor Perhotelan Indonesia: Moderasi Ukuran dan Usia Perusahaan - Jovan Febriantoko; Kartika Rachma Sari; Rosy Armaini (Politeknik Ganesha Medan, 2025)
This study aims to explore the impact of ESG disclosures on firm value and financial performance in the hotel, resort, and cruise subsector, with company size and age as moderating variables. The study population consists of companies in the hospitality industry listed on the Indonesia Stock Exchange. A purposive sampling method was employed, resulting in a sample of 32 companies that made complete ESG disclosures for the 2021-2022 period. Using panel data analysis, this study examines the relationship between ESG initiatives and firm value (FV) and financial performance (FP), moderated by company size and age. The findings reveal that ESG disclosures explain 82.15% of the variation in firm value (FV) and 87.19% of the variation in financial performance (FP), indicating a significant impact of ESG on enhancing company reputation and performance, particularly among younger companies, with six firms in the younger category. These findings highlight the importance of integrating ESG initiatives into the hospitality industry to improve operational efficiency, enhance stakeholder trust, and drive better financial outcomes. This research provides empirical evidence for managers to prioritize sustainability in business strategies, emphasizing its role in fostering long-term growth and competitiveness.